"New" medical education: perception of professor of an undergraduate program implemented from Mais Médicos Program (Research, Society and Development, 2022)
Introduction: Medical education is constantly changing in order to train medical professionals capable of intervening in the current needs of Brazilian health. In Brazil, this changing process was driven by Mais Médicos Program and the new National Curriculum Guidelines for medicine undergraduate. Objective: This study aimed to describe the perception of professors acting in an undergraduate medical program aligned with the Mais Médicos Program with regard to the "new" medical education in Brazil. Methods: This is a qualitative study, in which 18 medical educators of the aforementioned course. Data collection occurred through individual narrative interviews based on a guiding script. Data analysis was conducted by Hermeneutic-Dialectic. The following categories of analysis emerged: the course Pedagogical Course Project (PCP) and learning methodologies. Results: Among the difficulties for its curriculum implementation, there are cited the professionalization of the teaching role, the complexity of the activities, the scarceness of literature sources, and insecurity. These characteristics are added to the overcoming of the traditional undergraduate formation, which together diverge with the implementation of active teaching strategies, requiring medical trainers to be open to the changes that have been occurring in medical education. Conclusion: With this study, it was possible to identify professors' concerns and perceptions regarding the format of the course and its implementation process.